Improving systemic risk frameworks in South Korea - Lim, Jasper Seng Leong (2019)
Following the 2008 financial crisis, Korean regulators have been focused on addressing the shortcomings in their frameworks designed to monitor systemic risk in the financial system. In this paper, we show that the recently-developed measures: ∆CoVaR, MES, SRISK, and linear Granger-causality network can accurately detect systemic risk and identify systemically important financial institutions (SIFIs) in South Korea. Additionally, we identified two key contributing factors to systemic risk in Korea, namely: (1) high short-term foreign debt holdings of investment banks and (2) high leverage of commercial banks. Finally, we provide recommendations to the Bank of Korea (BOK) and the Financial Services Commission (FSC) on applying the ΔCoVaR, MES, SRISK, and the linear Granger-causality network to improve their frameworks in capturing systemic risk.